Urinary excretion of salicyluric and salicylic acids by non-vegetarians, vegetarians, and patients taking low dose aspirin. Issue 9 (27th August 2003) - Lawrence, J R; Peter, R; Baxter, G J; Robson, J; Graham, A B; Paterson, J R
Abstract : Aim: To compare amounts of salicyluric acid (SU) and salicylic acid (SA) excreted daily in the urine of non-vegetarians and vegetarians not taking salicylate drugs, and patients taking 75 or 150 mg aspirin/day. Methods: Urine excreted over 24 hours was collected from volunteers in the four groups. The volumes were recorded and the concentrations of SU and SA were determined electrochemically after separation by high performance liquid chromatography. Results: Significantly more SU was excreted daily by vegetarians (median, 11.01; range, 4.98–26.60 μmol/24 hours) than by non-vegetarians (median, 3.91; range, 0.87–12.23 μmol/24 hours), although amounts were significantly lower than those excreted by patients taking aspirin. Median amounts of SU excreted by patients taking 75 and 150 mg/day of low dose aspirin were 170.69 (range, 13.15–377.18) μmol/24 hours and 165.17 (range, 5.61–429.12) μmol/24 hours, respectively. The amount of SU excreted by patients taking either 75 or 150 mg of aspirin/day was not significantly different. Significantly more SA was excreted by vegetarians (median, 1.19; range, 0.02–3.55 μmol/24 hours) than by non-vegetarians (median, 0.31; range, 0.01–2.01 μmol/24 hours). The median amounts of SA excreted by vegetarians and the patients taking aspirin were not significantly different. Conclusions: More SU and SA is excreted in the urine of vegetarians than in non-vegetarians, consistent with the observation that fruits and vegetables are important sources of dietary salicylates. However, significantly less SU was excreted by vegetarians than patients taking aspirin, indicating that the daily intake of bioavailable salicylates by vegetarians is considerably lower than that supplied by a single 75 or 150 mg dose of aspirin.